1998
DOI: 10.1017/s0008413100020454
|View full text |Cite
|
Sign up to set email alerts
|

Contrastive Focus, French N-words and Variation

Abstract: The aim of this article is to argue that the similarities and differences in the interpretation of n-words (personne, rien, etc.) in two closely related dialects of French can be explained by considerations linked to lexical properties as well as to properties of contrastive stress in Universal Grammar. The minor lexical differences in the two systems are related to the fact that only in Standard French is a single negation reading ruled out when an adverbial negative marker bearing [+neg, −T, −Asp] features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…'Heavy' SNs, on the other hand, are, according to most accounts, XPs analyzed as specifiers of NegP (Pollock 1989, Bayer 1990, Zanuttini 1991see also Merchant 2000). Quebecois French, Bavarian, and Afrikaans exhibit NC with a heavy NM, as we see below (see Vinet 1998, Bayer 1990and den Besten 1986 see Haegeman 1995). 3 In Haegeman (1995) [Spec,NegP] is assumed to be always filled at s-structure, either by a contentive element (an n-word) or by a phonologically null expletive NEG-operator.…”
Section: Notesmentioning
confidence: 72%
“…'Heavy' SNs, on the other hand, are, according to most accounts, XPs analyzed as specifiers of NegP (Pollock 1989, Bayer 1990, Zanuttini 1991see also Merchant 2000). Quebecois French, Bavarian, and Afrikaans exhibit NC with a heavy NM, as we see below (see Vinet 1998, Bayer 1990and den Besten 1986 see Haegeman 1995). 3 In Haegeman (1995) [Spec,NegP] is assumed to be always filled at s-structure, either by a contentive element (an n-word) or by a phonologically null expletive NEG-operator.…”
Section: Notesmentioning
confidence: 72%
“…Recent work by Reed (1997) and Authier (1997), for example, have focused on a pronominalized form with aspectual effects, namely the French demonstrative pronoun ce which is used to encode the aspectual notions of perfectivity, unboundedness and nonhabituality. 17 For a detailed study of these facts in QF, which we assume are not completely unrelated to the ones discussed here, see Vinet (1998b) and Muller (1991:262±263 Interestingly, it can also be observed that the equivalent QF structures with ±tu pas in the grammar of SF can be paralleled by sentences where one finds either a lexically filled CP (with a Q operator (32a) or an E(valuative) operator (32b,c) ) cooccurring with a negative marker pas whose semantic property is not to negate the proposition:…”
Section: The Interpretation Of -Tu Pas In Quebec Frenchmentioning
confidence: 84%
“…NC sentences are not even ambiguous between a single and a double negative reading, as we would expect under the hypothesis that they are negative. In some NC languages, however, double negation readings may marginally arise with nwords, e.g in Spanish and Portuguese, in Que Âbe Âcois (Vinet 1998), and, to a very limited extent, in Hungarian (see Puska Âs 1998, where it is emphasised that not all speakers accept the marginal double negation readings). In French, we find a pattern of systematic ambiguity.…”
Section: Distinct Semanticsmentioning
confidence: 99%
“…(The NM may be either a Neg 0 -head, 88 transactions of the philological society 98, 2000 as in the examples in (1), or an XP, i.e. a specifier, as in Haitian Creole and Que Âbe Âcois French; see De Âprez 1997 andVinet 1998). Negative spread, on the other hand, involves the co-occurrence of two n-words to the exclusion of the NM.…”
mentioning
confidence: 99%